Urgency of a New Dawn : Prison Thoughts and Reflections - Nfor, N. Nfor (Book collections on Project MUSE., 2016)
Urgency of a New Dawn is the cry of most Southern Cameroonians against those who they experience to be an oppressive, Machiavellian, hostile, parasitising, captor-like, secessionist, assimilationist, discriminatory, and dehumanising la Republique du Cameroun, to which they were annexed through misleading UN and UK politics and Politics as a condition toward their independence from the UK in 1961. Extrapolating only on these two territories, Urgency of a New Dawn is no less the sweeping story of one too many other peoples across Africa, tormented by the heedless partitioning of the continent by colonisers and the consequential neo-patrimonial and ethnic African Politics and politics of belonging. Forced either into spaces that were never theirs, or pushed out of spaces that they struggle to claim and/or prove theirs, many African peoples today find themselves engaging in endless battles, not against colonisers but against fellow black Africans, for the survival of their essence, their culture, languages, traditions, dignity, modes of being and identification, right to equality, and freedom.